ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN PERUMAHAN DI KABUPATEN BERAU: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN PERUMAHAN DI KABUPATEN BERAU - dawami buchori (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2018)
ABSTRACT In this case the residential area of Saoda Sambaliung District is one of the right alternatives, both in terms of price, convenience facilities and strategic location located in streets Bayanuddin gang Akasia Mandiri Sambaliung District can meet the expectations of the community will a housing needs. Analyzer used is multiple linear regression. Respondents of this research are residents of Saoda sub-district of Sambaliung. The result of analysis shows that price, location, income and substitution price have an effect on the decision of house purchase. From the test of coefficient of determination known that 68.60% of the variations that occur in the purchase decision variables are simultaneously influenced by the variable perception of price, location, income and price substitution. While the rest of 31.40% influenced by other factors. From the results of this study found that the factor of the facility is very influential in the purchase of the house. Judging from the amount of coefficient affecting the decision to determine the purchase is the income of 0.443%, the location of 0.340%, the price of 0.268% and the substitution price of 0.283%.